A facile method of removing several common surface-enhanced Raman scattering probe molecules adsorbed on Ag with sodium borohydride solution. (10th June 2015) - Yang, Yongan; Wang, Yuyang; Zhang, Xiaoyong; Qi, Guohua; Xu, Shuping; Xu, Weiqing
Abstract: Ag nanoparticles and nanostructured surfaces have been widely used as surface-enhanced Raman scattering (SERS) substrates, which can enhance the Raman signals when molecules are adsorbed on the surface of Ag by the effect of Ag-thiol bonds. In this paper, we propose an efficient method to remove the molecules adsorbed on Ag with sodium borohydride solution, providing a protocol to realize a reproducible and practicable Ag SERS substrate. A theoretical density function theory approach has been used to explain the mechanism of desorption.